Revisit dogmas on origins and ecology of emerging and re-emerging infectious Diseases : arboviruses in africa - (:unkn) unknown (My University, 2021)
Arboviruses are responsible for a significant public health burden throughout the world with over 150 viral species having capacity to cause disease in humans. Almost all of them are zoonotic and circulate between vertebrate hosts and hematophagous vectors such as mosquitoes, ticks and midges. Almost all are maintained in sylvatic transmission cycles involving wildlife. Ever since, arboviruses have caused outbreaks around the world and new arboviruses have emerged from their sylvatic reservoirs such as West Nile, Usutu and Zika viruses as the most recent examples. Understanding the emergence of arboviral disease in humans and developing surveillance methods to predict its occurrence depends upon the understanding of the ecology of the different arboviruses and their life-cycles. During enzootic periods, arboviruses survive via sylvatic life cycles which can involve a variety of species of which many are currently not identified, especially in Africa. It is unclear which and how many animal species can contribute to the maintenance of arboviruses in nature, nevertheless the sylvatic/zoonotic cycles of many mosquito-borne viruses are presented with arboreal mosquitos feeding on non-human primates (NHPs). However, this is can be extremely oversimplified because their population numbers and number of susceptible animals at any time, are not enough to maintain sylvatic cycles and other mammals are probably also involved. Thus, the goal of this project is to provide new insights in the animal reservoir or amplifier hosts, the ecology of arboviruses in African countries and document extent of infection rates in animals. We developed a serological tool that allows simultaneous detection of IgG antibodies to multiple arboviruses in a single biological sample. With this highly sensitive and specific multiplex immunoassay, we screened more than 6000 samples from a wide diversity of primate and bat species across Central and West Africa. Primates from Cameroon and
Keywords: African Research